Shortest Path Search for PDAM Pipeline Leaks Using Dijkstra Algorithm - Irsyada, Rahmat; Audytra, Hastie (Proceeding International Conference on Religion, Science and Education, 2022)
PDAM pipeline leaks are a major problem, both financially and in the short supply of water to customers. This problem resolves to immediately overcome the existing leak. But the problem is how to determine which parts of the control are closest so that improvements become optimal without wasting a lot of money. One of the methods used to solve the problem with the technique of solving algorithm problem, Dijkstra. The Dijkstra algorithm is an algorithm commonly used to search the shortest route. Based on the problem, the program made the shortest route search program for PDAM pipeline leaks using the Dijkstra algorithm.